Artemisinin Targets Transcription Factor PDR1 and Impairs Candida glabrata Mitochondrial Function - Pan Zhu; Chaoping Yue; Xin Zeng; Xiulai Chen (MDPI AG, 2022)
A limited number of antifungal drugs, the side-effect of clinical drugs and the emergence of resistance create an urgent need for new antifungal treatment agents. High-throughput drug screening and in-depth drug action mechanism analyzation are needed to address this problem. In this study, we identified that artemisinin and its derivatives possessed antifungal activity through a high-throughput screening of the FDA-approved drug library. Subsequently, drug-resistant strains construction, a molecular dynamics simulation and a transcription level analysis were used to investigate artemisinin's action mechanism in Candida glabrata. Transcription factor pleiotropic drug resistance 1 (PDR1) was an important determinant of artemisinin's sensitivity by regulating the drug efflux pump and ergosterol biosynthesis pathway, leading to mitochondrial dysfunction. This dysfunction was shown by a depolarization of the mitochondrial membrane potential, an enhancement of the mitochondrial membrane viscosity and an upregulation of the intracellular ROS level in fungi. The discovery shed new light on the development of antifungal agents and understanding artemisinin's action mechanism.